Touching spirit bear eaudiobook - Mikaelsen, Ben (Spirit Bear, 2007)
Read by Lee Tergesen Approx. 6 hours 4 cassettes When he brutally attacks a classmate his punishment is an alternative path based on a Native American tradition called the Circle Justice. Banished to a remote Alaskan island, Cole's rage and isolation lead him to another brazen attack. This time, his intended victim is the Spirit Bear of Native American legend—and the clumsy assault ends with Cole mauled nearly to death. Rescuers arrive to save Cole's life, but it is the attack of the Spirit Bear that is the start of Cole's long journey to accepting responsibility for his life and saving his soul.